Teachers’ Methods, Content Knowledge and Learners’ Attitudes Towards Learning Physics in Uganda - Lugolole, Robert; Bazirakye, Thadeo K.; Kibirige, Israel; Batiibwe, Marjorie S. K.; Sentongo, John (Unnes Science Education Journal, 2023)
Secondary school learners have negative attitudes towards physics. This study investigated the relationship between learners’ attitudes towards physics and teachers’ methods and content in teaching Physics. A cross-sectional research design deploying a mixed method was used with 19 teachers and 327 learners. A questionnaire for learners and an interview guide for teachers were utilised to collect data. While thematic analysis was used for the qualitative data, descriptive statistics, Pearson correlation and regression analysis were used for quantitative data. Three themes emerged from the qualitative data: excitement, engagement, and demotivation. The quantitative results show that teachers’ PK and PCK enhanced learners’ attitudes towards physics. A regression analysis revealed that PK and PCK accounted for most variations, while CK had the least, suggesting a clear importance of pedagogy in influencing learners’ attitudes towards physics. This study recommends designing modules in PK and PCK with real-life challenges to enhance learners’ attitudes toward physics.